I am pretty sure that B is the answer
Answer: (f-g)(2)=14
Step-by-step explanation:
(f – g) (-2) means the same as subtracting f(2) and g(2). Since we are given f(x) and g(x), we can use them to solve. There are two ways to solve. One is to find f(2) and g(2), and then subtract them. Another way is to do (f-g)(x), then plug in x=2. I will show both methods.
Method 1
f(2)=3(2)²+1 [exponent]
f(2)=3(4)+1 [multiply]
f(2)=12+1 [add]
f(2)=13
g(2)=1-(2) [subtract]
g(2)=-1
(f-g)(2)=13-(-1) [subtract f(2) and g(2)]
(f-g)(2)=14
--------------------------------------------------------------------------------------------------------
Method 2
(f-g)(x)=3x²+1-(1-x) [distribute -1]
(f-g)(x)=3x²+1-1+x [combine like terms]
(f-g)(x)=3x²+x
(f-g)(2)=3(2)²+2 [plug in x=2, exponent]
(f-g)(2)=3(4)+2 [multiply]
(f-g)(2)=12+2 [add]
(f-g)(2)=14
--------------------------------------------------------------------------------------------------------
Now, we know that (f-g)(2)=14. We confirmed this with both methods.
Answer:
slope = 3
Step-by-step explanation:
The equation of a line in slope- intercept form is
y = mx + c ( m is the slope and c the y- intercept )
Given
9x - 3y = - 54 ( subtract 9x from both sides )
- 3y = - 9x - 54 ( divide all terms by 0 3 )
y = 3x + 18 ← in slope- intercept form
with slope m = 3
Parallel lines have equal slopes, thus
slope of parallel line is 3
Answer:
$900
Step-by-step explanation:
the steps are above